Principal Transformational Leadership Style on Teacher Performance - Marsasanda Andarin; Hasan Hariri; Siti Rahma Sari; Handoko Handoko (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2025)
Improving the quality of education depends greatly on enhancing teacher performance, which remains a persistent challenge in many schools. Several studies indicate that low motivation, limited creativity in teaching, and minimal teacher participation in decision-making continue to hinder educational progress. This review examines how the transformational leadership style of principals influences teacher performance through motivation, commitment, discipline, and the development of a positive school culture. This study used a qualitative descriptive literature review to analyze eighteen peer-reviewed publications issued between 2018 and 2024. The review process included identifying, selecting, and synthesizing research related to principal leadership and teacher performance. The findings show that transformational leadership directly improves teacher motivation, job satisfaction, and commitment to the profession. It also reveals that these effects are reinforced by mediating factors such as work discipline, intrinsic motivation, and teacher commitment. Furthermore, a supportive school culture strengthens the overall impact of leadership, creating an environment that encourages collaboration, trust, and shared goals. The results suggest that transformational leadership is a key factor in promoting teacher professionalism and the overall quality of education. Principals who act as visionary leaders, motivators, and mentors can build a culture of continuous improvement within their schools. The study recommends further empirical research using longitudinal and comparative approaches to validate these findings and explore how different leadership frameworks can be integrated to support sustainable educational excellence.